Parfois’ stock replenishment system - a new approach - Castro, Ana Beatriz Bento Coelho Martins de (2019)
The fast fashion business model has transformed the retail industry. The incessant emergence of new trends makes it challenging to accurately forecast sales which results in inventory inaccuracies ultimately compromising sales. The present work project proposes a new approach to the Parfois’ stock replenishment system, adding value to the company. Considering the characteristics of the environment in which Parfois operates, and since the company is a large fashion retailer, a different methodology was assessed and compared with the one currently in use by the company. The results suggest a new model proposal which may provide a better solution for the current Parfois’ stocking process.